Pakistan statistical yearbook. - Pakistan Statistical Yearbook; Pakistan. Central Statistical Office (Karachi Manager of Publications, 1952)
Annual
Issued by the Central Statistical Office.
Vols. for 1952- include comparative statistics for previous years.
Keywords: Pakistan -- Statistics